Study of the geochemical affinities of the mercury and other trace elements in coals from the Carboniferous of the Iberian Peninsula - Moura, Helena Raquel Oliveira (2016)
Dissertação de Mestrado em Geociências, Recursos Geológicos, apresentada à Faculdade de Ciências e Tecnologia da Universidade de Coimbra.